Merry Morticians. - Chu, Zoe Li Qi. (2008)
ACCOMPANIED BY: VIDEO (DVD), PRESS KIT (CD) – PLEASE APPROACH ACRC LOAN COUNTER. A visual depiction of warped love and betrayal, in a society where morals are rare and themes of guardianship are explored in depth.